Dielectric properties for rapid on-site detection and screening of halal and non-halal foods - Omar, Fatin Nordalila (2014)
Halal verification has become increasingly important especially to the Muslim communities and very challenging nowadays due to the unavailability of a robust and rapid method to detect non-halal products. A potential method for detection and discrimination of products for halal authentication using dielectric properties has been investigated in this study. With regards to the interests of consumers particularly on food intake, this study focuses on several types of primary alcohol, commercial beverages and meat. The aim of this work is to characterize the dielectric response of alcohol and meat samples by using the dielectric properties, which is as potentially rapid on-site determination for halal and non-halal products. Measurements were made with frequency domain technique from 500 MHz to 50 GHz by means of an openended coaxial probe connected to Agilent Professional Network Analyzer (PNA-X) N5245A. For alcohol, the results show dielectric properties of alcohol can be detected until lowest concentration of 0.1% since standardization of alcohol content allowed by JAKIM is < 0.5 %. Frequency 10 GHz – 25 GHz was found to give good separation of graph for different concentration of ethanol solution. Data evaluation of several alcoholic and non-alcoholic beverages were supported with Gas Chromatography Mass Spectrometry (GC-MS) method in order to relate the polarity of volatile compounds and polarization effects in dielectric signal. Calculation of the parameter ε ∞, ε′s, ε′s - ε ∞ and H in the proposed Debye model combined with Higasi’s equation of relaxation time provided good agreement to the experimental data. Among the parameters, ε′s - ε ∞ (R2=0.9964) and H (R2=0.9857) gave the best regression line to be used as concentration detection. Raw beef, pork and chicken meat were characterized by dielectric over the same frequency range and two prominent peaks identified as Peak A (at 7 GHz) and Peak B (at 30 GHz) were found in pork and mix meat samples. Next, parameter of penetration depth, dp also showed good effects between heated pork and other meats since the correlation between moisture content and dp is higher (R2=0.98). The emergence of Peak B was continuous in sterilized pork, heated pork, porcine gelatin and pork in can. The consistency of this peak in all pork-based samples in this study shows it can be the potential marker to discriminate non-halal (pork) and halal meat since it was not seen in beef and chicken. It is believed there are some constituent species in pork sample does not destroyed even high temperature were subjected on it. This finding proves dielectric technique could be utilized for rapid on-site verification for any meat samples by detecting the significance Peak B at frequency of ~30 GHz. This technique also can reduce the analysis time and provide high accuracy result for initial screening purpose.